A Statistical Based Estimation of Candesartan and Simvastatin Using Simultaneous Estimation, First Order Derivative and Q Value Method by UV Spectrophotometry - Jaman, Sarwar; Maity, Arindam; Sarkar, Saptarshy; Mondal, Anjan; Banerjee, Bishal; Behera, Padmacharan; Dey, Suddhasattya; Mondal, Arijit (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background: When combined with simvastatin, candesartan is a more potent antihypertensive medication than statins by itself. Therefore, to estimate Candesartan and Simvastatin concurrently in the mixture, a quick, economical and straightforward analytical method is needed. In order to evaluate candesartan and simvastatin using UV spectrophotometry, the current study set out to create and statistically validate an estimating approach utilizing simultaneous estimation, the first order derivative method and the Q ratio method. Materials and Methods: All the methods were validated by following the ICH Q2 (R1) guidelines. Phosphate buffer of pH 7 was selected as a solvent because Simvastatin and Candesartan were soluble in it and provided stable absorbance with it. For simvastatin and candesartan, the wavelengths chosen were 239 nm and 250 nm, respectively. The accuracy, precision, robustness, linearity, limit of detection and limit of quantification of the suggested approach were all validated. ONE way ANOVA was applied Results: Simvastatin and candesartan concentrations varied from 2-10 μg/mL and 1-5 μg/mL, respectively, demonstrating a linear approach with a correlation coefficient (R2) of 0.999. All three methods were used to analyse the synthetic mixture and the percentage mean assay for simvastatin and candesartan was 100±2%. The statistical validation of the method revealed a lower percentage RSD, demonstrating its precision, accuracy and robustness. Conclusion: For the simultaneous estimation of candesartan and simvastatin, all of the approaches were found to be accurate, simple, precise and repeatable. Candesartan and simvastatin in pharmaceutical dose forms can be quantified using these new analytical techniques.
Keywords: Analytical method validation; Candesartan; First order derivative method; Q-ratio method; Simultaneous equation method; Simvastatin; UV-visible spectroscopy